Unique cellular network formation guided by heterostructures based on reduced graphene oxide - Ti3C2Tx MXene hydrogels. (1st October 2020) - Wychowaniec, Jacek K.; Litowczenko, Jagoda; Tadyszak, Krzysztof; Natu, Varun; Aparicio, Claudia; Peplińska, Barbara; Barsoum, Michel W.; Otyepka, Michal; Scheibe, Błażej
Abstract: Two-dimensional (2D) materials remain highly interesting for assembling three-dimensional (3D) structures, amongst others, in the form of macroscopic hydrogels. Herein, we present a novel approach for inducing chemical inter-sheet crosslinks via an ethylenediamine mediated reaction between Ti3 C2 Tx and graphene oxide in order to obtain a reduced graphene oxide-MXene (rGO-MXene) hydrogel. The composite hydrogels are hydrophilic with a stiffness of 20 kPa. They also possess a unique inter-connected porous architecture, which led to a hitherto unprecedented ability of human cells across three different types, epithelial adenocarcinoma, neuroblastoma and fibroblasts, to form inter-connected three-dimensional networks. The attachments of the cells to the rGO-MXene hydrogels were superior to those of the sole rGO-control gels. This phenomenon stems from the strong affinity of cellular protrusions (neurites, lamellipodia and filopodia) to grow and connect along architectural network paths within the rGO-MXene hydrogel, which could lead to advanced control over macroscopic formations of cellular networks for technologically relevant bioengineering applications, including tissue engineering and personalized diagnostic networks-on-chip. Statement of Significance: Conventional hydrogels are made of interconnected polymeric fibres. Unlike conventional case, we used hydrothermal and chemical approach to form interconnected porous hydrogels made of two-dimensional flakes from graphene oxide and metal carbide from a new family of MXenes (Ti3 C2 Tx ). This way, we formed three-dimensional porous hydrogels with unique porous architecture of well-suited chemical surfaces and stiffness. Cells from three different types cultured on these scaffolds formed extended three-dimensional networks – a feature of extended cellular proliferation and pre-requisite for formation of organoids. Considering the studied 2D materials typically constitute materials exhibiting enhanced supercapacitor performances, our study points towards better understanding of design of tissue engineering materials for the future bioengineering fields including personalized diagnostic networks-on-chip, such as artificial heart actuators. Graphical abstract: Image, graphical abstract